Manajemen Waktu dan Kecemasan Matematis: Studi Korelasional Terhadap Capaian Prestasi Belajar Siswa - Rina; Sakinah Ubudiyah Siregar; Nurlina Ariani Hrp (JNPM (Jurnal Nasional Pendidikan Matematika), 2026)
This study aims to analyze the simultaneous correlation between time management and mathematical anxiety toward students' academic achievement, focusing on the unique phenomenon where high anxiety levels coexist with optimal academic performance. Employing a quantitative approach, this research involved 32 eighth-grade students at MTsN 2 Labuhanbatu, selected through purposive sampling. Data were collected via structured questionnaires and examination records, then analyzed using partial and simultaneous regression tests. The findings demonstrate that time management and mathematical anxiety significantly contribute to academic achievement (F = 89.874; p < 0.005). Partially, both time regulation and anxiety proved to be significant predictors of students' learning success. Uniquely, anxiety in this context does not act as a hindrance but functions as a motivational catalyst that enhances learning intensity. These results imply that proper anxiety management, combined with disciplined time management, can optimize students' academic performance in mathematics learning.